Bi-Univalent Problems Involving Generalized Multiplier Transform with Respect to Symmetric and Conjugate Points - Jamiu Olusegun Hamzat; Matthew Olanrewaju Oluwayemi; Alina Alb Lupaş; Abbas Kareem Wanas (Fractal and Fractional, 2022)
In the present article, using the subordination principle, the authors employed certain generalized multiplier transform to define two new subclasses of analytic functions with respect to symmetric and conjugate points. In particular, bi-univalent conditions for function <semantics>f(z)</semantics> belonging to these new subclasses and their relevant connections to the famous Fekete-Szegö inequality <semantics>|a3−v<msubsup>a22</msubsup>|</semantics> were investigated using a succinct mathematical approach.